Analisa Pemanfaatan Sampah Organik Sayuran Rumah Tangga Menjadi Pupuk Cair Organik - Sira Albina; Petrus Benny; Shanti Veronica Br Siahaan (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
This study aims to utilize household vegetable waste to become liquid organic fertilizer in Cipta Karya Village, Kec. Betung River, Kab. Stuffed. The data analysis method used in this study uses a qualitative descriptive method. The object of this research was carried out in the Cipta Karya Village community, Kec. Betung River, Kab. Bengkayang where the samples were taken were the result of the direct practice of the community from Riam Palayo Hamlet chaired by the Hamlet Head. Data collection techniques using literature studies on the process of making Liquid Organic Fertilizer, Minister of Agriculture regulations, quality standards, benefits of liquid organic fertilizer, raw materials for making liquid organic fertilizer, how to use it, and about microorganisms that help the fertilizer fermentation process. Liquid organic fertilizer from various types of household waste that has previously been chopped and then added with an effectivate microorganism bioactivator (EM4) as an ingredient to speed up the fermentation process. To produce better organic liquid fertilizer, it takes 3-4 weeks from the first day of fertilizer production.